The Effect of Digital Divide on Individual Performance and Village Financial Reporting Quality - Alam, Muhammad Dimar (Research Horizon, 2025)
The digital divide remains a crucial issue affecting financial transparency and accountability in village governance. Despite the widespread implementation of the Village Financial System (SISKEUDES) in Indonesia, disparities in digital access and literacy may hinder the effectiveness of financial reporting. This study examines the relationship between the digital divide on the quality of village financial reports, emphasizing the mediating role of individual performance in SISKEUDES implementation. This research employs a quantitative approach using a survey-based design. The population consists of villages in Malang Regency. Data were collected through questionnaires and analyzed using multiple regression and path analysis. The findings indicate that the digital divide positively influences individual performance, and individual performance positively impacts the quality of financial reports. Moreover, individual performance partially mediates the relationship between the digital divide and financial reporting quality. The findings emphasize the need for targeted digital literacy programs and infrastructure development to optimize SISKEUDES implementation and enhance financial transparency in village governance.